Realidade aumentada para posicionamento de equipamentos em ensaios de acústica em campo - Rossatto, Fernanda Catarina (Universidade do Vale do Rio dos Sinos, 2023)
Due to the urbanization and verticalization processes of cities, urban noise is one of the main agents of pollution in large cities and is considered a public health problem by the World Health Organization (WHO). In an attempt to minimize the effects of urban noise, studies have been conducted to improve the understanding of facade acoustics, in order to reduce the impact of environmental noise inside buildings. To analyze this impact, ABNT NBR ISO 16283-3:2021 sets requirements for evaluating the performance of facade systems in the field. This is a complex process that requires careful placement of equipment - sound source and sound analyzer - and consideration of all variables at the site that may influence the test, such as the design and implementation of the building. Given the increasing use of augmented reality technology and its advantages in various sectors, this work aims to explore the feasibility of using Augmented Reality as an auxiliary tool for conducting acoustic tests in the field, with emphasis on assisting in equipment placement. For this purpose, five case studies were analyzed, in which the distance from the facade was measured in two ways: manually (using dimensional equipment) and using the Augin augmented reality app. The distance measurements were statistically analyzed using analysis of variance (ANOVA). It was observed that it is not recommended to use only the Augin app for the complete acoustic performance test, as it was not very accurate in terms of the sound source position, which could result in not meeting the minimum distance requirement specified in ABNT NBR ISO 16283-3:2021. However, augmented reality allows for a preliminary analysis of any test location - using the geometry template and a physical path of the Reference Tracker. This preview of the testing process is crucial as it enables the identification and evaluation of potential sources that could affect the test results.
Keywords: Desempenho acústico; Ensaio em campo; Realidade aumentada; ANOVA; Acoustic performance; Field test; Augmented reality; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo